Digital Transformation: Building a Literacy Bridge for the Zoomers Generation through Digital Library Needs Analysis - Yeti Komalasari; Lisa Yiharodiyah; Muhammad Kristiawan (Journal of Innovation in Educational and Cultural Research, 2023)
This study aims to examine how digital libraries can best assist the literacy of the Zoomers generation. This mixed-method study combined a survey approach with qualitative and quantitative descriptive research. The researchers, who were actively engaged in the research, were the research instrument. The Palembang Aviation Polytechnic's director, informant II, Deputy Director I, the Head of Academic Administration and Youth, and Informant IV, the Head of the Library Unit, were the only individuals or organizations that served as research objectives and sources of information for this study's informant determination. All 327 library members of Palembang Aviation Polytechnic comprised the study's population, and 282 cadets were chosen as the study's sample. The study's findings allow for measuring the Palembang Poltekbang Library's existing state and analyzing user demands for addressing literacy needs through open interviews and research questions presented in Google Forms. To describe the distribution and frequency of each variable, the data analysis performed in this study was univariate using the SPSS series 24 application. In the change in reading culture variable, 47.3% (133 respondents) agree that the internet is accessed more often than physical books, and in the educational literacy needs variable, 56.7% (160 respondents) strongly agree that the internet is the main source of information search, in the need for educational literacy resources variable, there are 160 respondents who agree, and the information technology readiness variable. The results of the interviews support the findings of the quantitative data processing in this study, which show that there is a shift in reading culture from print books to e-books and current library developments have changed from traditional libraries to digital libraries. Digital libraries are needed for the literacy needs of library users and support the fulfillment of aspects of accreditation libraries and further needs analysis is needed from other supporting areas.